To evaluate the expression (a^2 - bc + 4a) / c, we substitute the given values for a, b, and c.
First, calculate a^2:
a^2 = 6^2 = 36
Now, calculate 4a:
4a = 4 * 6 = 24
Next, calculate bc:
bc = 3 * 8 = 24
Now, substitute these values into the expression and evaluate:
(36 - 24 + 24) / 8
Simplify the numerator:
36 - 24 + 24 = 36
Now, divide the numerator by c:
36 / 8 = 4.5
Therefore, when a = 6, b = 3, and c = 8, the value of (a^2 - bc + 4a) / c is 4.5.
Evaluate:
a2 - bc + 4a divided by c.
a = 6
b = 3
c = 8
3 answers
Give me an exact answer please
Certainly! To find the exact answer, we will substitute a = 6, b = 3, and c = 8 into the expression (a^2 - bc + 4a) / c.
First, calculate a^2:
a^2 = 6^2 = 36
Next, calculate bc:
bc = 3 * 8 = 24
Now, substitute these values into the expression and evaluate:
(36 - 24 + 4a) / c
Substituting a = 6:
(36 - 24 + 4(6)) / 8
Simplify the numerator:
36 - 24 + 4(6) = 36 - 24 + 24 = 36
Now, divide the numerator by c:
36 / 8
The exact answer is 36/8, which cannot be simplified further.
First, calculate a^2:
a^2 = 6^2 = 36
Next, calculate bc:
bc = 3 * 8 = 24
Now, substitute these values into the expression and evaluate:
(36 - 24 + 4a) / c
Substituting a = 6:
(36 - 24 + 4(6)) / 8
Simplify the numerator:
36 - 24 + 4(6) = 36 - 24 + 24 = 36
Now, divide the numerator by c:
36 / 8
The exact answer is 36/8, which cannot be simplified further.